Tackling Egypt’s rising food insecurity in times of transition - Al-Riffai, Perrihan (2013)
Presentation by Perrihan Al-Raffai at the event: “Tackling food security and nutrition in Egypt: challenges and opportunities” Launch of the findings from the Household, Income, Expenditure and Consumption Survey , Tuesday 21 May in Cairo, Egypt.